The behavioural response of migrating humpback whales to a full seismic airgun array. Issue 1869 (13th December 2017) - Dunlop, Rebecca A.; Noad, Michael J.; McCauley, Robert D.; Kniest, Eric; Slade, Robert; Paton, David; Cato, Douglas H.
Abstract : Despite concerns on the effects of noise from seismic survey airguns on marine organisms, there remains uncertainty as to the biological significance of any response. This study quantifies and interprets the response of migrating humpback whales ( Megaptera novaeangliae ) to a 3130 in 3 (51.3l) commercial airgun array. We compare the behavioural responses to active trials (array operational; n = 34 whale groups), with responses to control trials (source vessel towing the array while silent; n = 33) and baseline studies of normal behaviour in the absence of the vessel ( n = 85). No abnormal behaviours were recorded during the trials. However, in response to the active seismic array and the controls, the whales displayed changes in behaviour. Changes in respiration rate were of a similar magnitude to changes in baseline groups being joined by other animals suggesting any change group energetics was within their behavioural repertoire. However, the reduced progression southwards in response to the active treatments, for some cohorts, was below typical migratory speeds. This response was more likely to occur within 4 km from the array at received levels over 135 dB re 1 µPa 2 .s.